2015
DOI: 10.1097/inf.0000000000000892
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus Infection in Jordanian Children

Abstract: Background Human metapneumovirus (HMPV) is a leading cause of acute respiratory tract infection (ARTI) in young children. Our objectives were to define HMPV epidemiology and circulating strains and determine markers of severe disease in Jordanian children. Methods We conducted a prospective study March 16, 2010-March 31, 2013 using quantitative RT-PCR to determine the frequency of HMPV infection among children <2 years old admitted with fever and/or acute respiratory illness to a major government hospital in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 45 publications
10
21
2
Order By: Relevance
“…Aliquots were shipped on dry ice to Nashville, Tennessee, USA, and were tested by RT-PCR for 11 viruses: RSV; human rhinovirus (HRV); human metapneumovirus (HMPV); influenza (influenza) A, B and C; parainfluenza virus (PIV) 1, 2 and 3; adenovirus (AdV) and Middle East respiratory syndrome coronavirus (MERS-CoV). [14][15][16] Blood was placed directly onto filter paper and air dried for ≥30 min before storage at room temperature and kept dry through shipment to ZRT Laboratory (Beaverton, Oregon, USA) for 25(OH)D (vitamin D) level measurement (techniques published previously). 17 statistical analysis Descriptive statistics were presented as frequency (percentage) or median and IQR where appropriate.…”
Section: Laboratory Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Aliquots were shipped on dry ice to Nashville, Tennessee, USA, and were tested by RT-PCR for 11 viruses: RSV; human rhinovirus (HRV); human metapneumovirus (HMPV); influenza (influenza) A, B and C; parainfluenza virus (PIV) 1, 2 and 3; adenovirus (AdV) and Middle East respiratory syndrome coronavirus (MERS-CoV). [14][15][16] Blood was placed directly onto filter paper and air dried for ≥30 min before storage at room temperature and kept dry through shipment to ZRT Laboratory (Beaverton, Oregon, USA) for 25(OH)D (vitamin D) level measurement (techniques published previously). 17 statistical analysis Descriptive statistics were presented as frequency (percentage) or median and IQR where appropriate.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…setting A government hospital serving low-income and middle-income population in Amman, Jordan. Participants Children under 2 years of age hospitalised with fever and/or respiratory symptoms (n=3168) from 16 March 2010 to 31 March 2013. Children with chemotherapy-associated neutropenia and newborns who had never been discharged after birth were excluded from the study.…”
mentioning
confidence: 99%
“…Age is one of the major factors influencing disease severity, as evidenced by an increased rate of hospitalizations in infants Ͻ5 months of age, who have prolonged stays in the intensive care unit (ICU), being approximately twice as susceptible as infants 6 to 11 months of age and five times more susceptible than the average for children Ͻ5 years old (18). As for children, elderly individuals also show increased hospitalization rates and prolonged stays in the ICU (12,13,(47)(48)(49)(50)(51)(52)(53)(54). In agreement with this notion, recent studies demonstrated that an important fraction (up to 95%) of children infected with HMPV have no comorbidities and are otherwise healthy (51,53), suggesting that age alone is a major risk factor.…”
Section: Factors Contributing To Hmpv Disease Severitymentioning
confidence: 99%
“…8,17 Viruses from each subgroup are capable of causing severe LRI, and different subgroup viruses have not been associated convincingly with differing severity of disease. 18,19 In most studies of patients with acute respiratory tract infection, the percentage of HMPV detection varies from 6% to 25%. HMPV infection usually causes clinical disease; the virus is rarely detected in asymptomatic children.…”
Section: Human Metapneumovirusmentioning
confidence: 99%
“…Dual infection with RSV and HMPV increased the risk of severe disease and pediatric intensive care unit admission compared to RSV alone in one small study, 86 but this finding was not confirmed by subsequent larger reports. 19,8789 …”
Section: Hmpv In Preterm Infantsmentioning
confidence: 99%